Reformulasi Haul Zakat di Masa Pandemi dalam Tinjauan Empat Mazhab - Andi Muh. Taqiyuddin BN; Abdul Qadir Gassing; Muammar Muh. Bakry (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The major objective of this research was to investigate the concept of Zakatâ€™s haul during the pandemic based on the opinions of four big Imams of Islam. In addition, this research also aimed to know the law of expediting the zakat before its haul. The methodological approach taken in this research was qualitative approach by using the library research method. The scientific approaches employed by the researcher were language and normative juridical approaches. This study indicated two major findings. Firstly, in general, it was apparent that no requirements are needed for Zakatâ€™s haul on agricultural and fruit according to the majority of four scholars. While Hanafiyyah argued that one-year haul is a requirement for zakat including on agricultural products and fruits, MÄlikiyyah and Syafi'iyyah contrastingly suggested that the completion of one year (haul) is a mandatory condition for zakat only on goods such as gold and silver, produces, and livestock and not for the materials such as minings, inventions, and agricultural products. In the similar vein, Hanabilah suggested that one-year haul requirement is only given on gold, silver, livestock and produces. Other types such as fruits, agricultural products, mining goods, ancient relics are not required to complete one-year haul. Secondly, it is worth noticing that despite the differences, the opinions of the four Imams regarding the importance of expediting the zakat payments are the same. It should be paid based on the condition of its Haul. Several implications were drawn from this research. Firstly, theoretically, there are no disputes among the opinions of four Imams regarding the law of immediacy on zakat payments. However, the difference in the understanding of their followers and certain Muslim communities that may causes various contradictions in understanding the issue. Secondlt, practically, it is expected for all the related parties such as BAZNAS (Zakat Management Body) to educate people related to the wrong paradigm occurring among muslims in Indonesia.